Unlocking Mathematical Creativity: How Students Solve Open-Ended Geometry Problems - Simamora, Rustam Effendy; Kamara, Jean Gloria (Jurnal Pendidikan MIPA, 2024)
Abstract: Mathematical creativity has become increasingly significant in education, emphasizing originality, innovative solutions, and informed decision-making. However, a notable research gap exists in understanding how junior high school students creatively solve open-ended geometry problems. This study addressed this gap by exploring how students tackle such problems and constructing a mathematical creative process model. The research involved eight 7th-grade students from a public junior high school in North Kalimantan, Indonesia. A qualitative research approach, a case study strategy, was employed, utilizing observations, students’ answer sheets, and interview-based tasks to gather detailed insights into the students’ problem-solving processes. We implemented replicating the finding strategy and considered saturation to enhance the research quality. The findings revealed a six-phase model of the mathematical creativity process: reading, problem selection, and exploration; experiencing perception changes; looking for and generating ideas; undergoing incubation; implementing ideas; and verifying solutions. Self-regulation emerged as a crucial factor influencing student engagement and success in the creative process. Notably, the most creative student in this study demonstrated active actions during problem-solving through all phases, underscoring the importance of self-regulation. The study concludes that self-regulation and also incubation are pivotal in creative problem-solving. These insights provide valuable guidance for educators and researchers aiming to enhance mathematical creativity in the classroom, emphasizing the need for strategies that support self-regulation and innovative problem-solving abilities.        Keywords: geometry, mathematical creative process, open-ended problems, case-study.DOI: https://dx.doi.org/10.23960/jpmipa/v25i1.pp66-86